Accounting for Business / Third Edition - Atrill Peter; Harvey David; Mclaney Edward (Butterworth Heinemann, 2001)
An ideal book for undergraduate students on business and accounting courses who need a comprehensive understanding on financial accounting. Preface, Introduction to Accounting, The Role of Accounting in Business Decision Making, The Main Accounting Reports, The Balance Sheet, The Profit and Loss Account - Nature and Purpose, The Profit and Loss Account - Form and Content, The Measurement of Profit - Depreciation, Measurement Problems - Stock Valuation, Profit Measurement - Bad and Doubtful Debts: The Conventions, Practical Accounting, Practical Accounting - Ledger Accounts, Ledger Accounts - Further Complications, Accounting Systems, Accounting for Companies: The Regulatory Framework, An Introduction to the Accounts of Limited Companies, Accounting for Companies, The Regulatory Framework, The Account of Groups of Companies, The Analysis and Interpretation of Accounts, The Cash Flow Statement, The Use of Financial Statements for Planning and Decision Making, The Analysis of Financial Statements, The Conventions and the Conceptual Framework, Measurement of Profit and Capital Maintenance, Answer to Self - Assessment Questions, Index.